Recent approaches in guar gum hydrogel synthesis for water purification - Thakur, Sourbh; Sharma, Bhawna; Verma, Ankit; Chaudhary, Jyoti; Tamulevicius, Sigitas; Thakur, Vijay Kumar (Taylor and Francis, 2018)
Guar gum based hydrogels have evoked great attention in research as well as in industry for exploring miscellaneous applications in the field of water purification, medicine, agriculture, explosives, cosmetics, textile, paper, and food to name a few. In this article, latest modifications for developing guar gum based hydrogels and composite materials for water purification application are extensively reviewed. Regenerative nature of Guar gum hydrogels makes it a better choice for treating wastewater as well as other value-added applications. Moreover, nonionic nature makes guar gum an acceptable material for further modifications. In this article, we also present a brief discussion on structure and properties of guar gum.
Keywords: Guar gum; hydrogel; composites; dye adsorption; metal ion adsorption; water purification